2023
DOI: 10.3389/fchem.2023.1290619
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of grape (Vitis vinifera) leaves for bioactive compounds: novel green extraction technologies and food-pharma applications

Jyoti Singh,
Prasad Rasane,
Rajdeep Kaur
et al.

Abstract: Grape leaves, scientifically known as Vitis vinifera, the primary by-product obtained after the processing of grapes, are gathered in enormous amounts and disposed of as agricultural waste. For more sustainable agriculture and better food systems, it is crucial to investigate these byproducts’ nutritional values. The primary bioactive compounds present in grape leaves are quercetin, resveratrol, caffeic acid, kaempferol, and gallic acid, which favour pharmacological effects on human health such as antioxidant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…It is also well known that lactic acid bacteria can decompose quinic acid and malic acid, which may finally give them a metabolic predominance over other groups of microorganisms during the fermentation of plant raw materials [28][29][30]. Grapevine leaves are a rich source of bioactive compounds, including quercetin and resveratrol [20]. Quercitin has strong antimicrobial activity against both Gram-negative and Gram-positive bacteria; however, research indicates a low inhibitory effect in the case of microorganisms belonging to the Lactobacillus genus, which may result in a metabolic predominance of lactic acid bacteria in the microbial population in the presence of these compounds [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well known that lactic acid bacteria can decompose quinic acid and malic acid, which may finally give them a metabolic predominance over other groups of microorganisms during the fermentation of plant raw materials [28][29][30]. Grapevine leaves are a rich source of bioactive compounds, including quercetin and resveratrol [20]. Quercitin has strong antimicrobial activity against both Gram-negative and Gram-positive bacteria; however, research indicates a low inhibitory effect in the case of microorganisms belonging to the Lactobacillus genus, which may result in a metabolic predominance of lactic acid bacteria in the microbial population in the presence of these compounds [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits result from the presence of probiotic lactic acid bacteria that have a positive effect on gut health, as well as the presence of biologically active compounds, including antimicrobials (organic acids, bacteriocins). Additionally, during the fermentation process, the elimination of compounds toxic to human health, such as phytates and tannins, and the formation of beneficial catabolites may occur; as a result, the fermented products are classified as super-foods [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the number of polyphenols in red grapevine leaves is similar to that in red grape seeds. The leaf extracts reveal antioxidant, antimicrobial, and antitumor activities [ 88 ]. The chemical composition of grape leaves significantly fluctuates according to the development stage, but variety, harvesting period, environmental factors, and soil properties also change the phytochemical profile of the leaves [ 89 ].…”
Section: The Potential Of Viticulture By-products To Modulate Gut Mic...mentioning
confidence: 99%
“…The chemical composition of grape leaves significantly fluctuates according to the development stage, but variety, harvesting period, environmental factors, and soil properties also change the phytochemical profile of the leaves [ 89 ]. Although this viticulture waste is less valorized, studies have constantly shown the high antioxidant activity of leaf extracts, which could be due to the synergistic action of various bioactive compounds from different classes (polyphenols, tocopherols, carotenoids, and phytosterols) [ 88 , 89 ]. In recent work on grapevine leaves from 11 different types of vine varieties grown under the same agronomical conditions and in the same soil, Banjanin et al, 2021, revealed that flavonoids, total phenols, and carotenoids are the main bioactive compounds [ 90 ].…”
Section: The Potential Of Viticulture By-products To Modulate Gut Mic...mentioning
confidence: 99%
See 1 more Smart Citation